Effects Of Filler Loading And Different Preparation Methods On The Properties Of Cassava Starch Filled Natural Rubber Composites - Nguyen , Quang Duy (2012)

(untitled)
This project is concerned with the preparation methods of cassava starch/natural rubber composite. First, the effects of different cassava starch (CS) loading on the properties of natural rubber (NR) composites were investigated. CS/NR composites at different CS loading (5-25 phr) were compounded using a tworoll mill under room temperature. Results indicated that the scorch time and cure of CS/NR composites slightly reduced with increasing CS loading. However, the addition of CS reduced the maximum torque, thermal stability and mechanical properties of CS/NR composites. The optimum tensile strength and tear strength were obtained at 10 phr of CS and decreased considerably with higher CS loadings. Second, the effects of CS loading and preparation methods on properties of CS/NR composites have been investigated. Three types of preparation methods were used in this project namely; direct blending, co-coagulation, and freeze-drying. The CS/NR composites prepared by co-coagulation and freeze-drying methods exhibit better mechanical properties and thermal stability than CS/NR composites prepared by direct blending method. In all methods studied, the hardness increased with increasing CS loading. Moreover, the morphological study confirmed that the freezedrying method improved the dispersion of CS in NR matrix than direct blending and co-coagulation methods.